Implementation of Bhinneka Tunggal Ika Values in Civic Education Learning at SD Negeri 001 Sangatta Utara - Farida Catur Wahyu Anggriyani; Widia Ningsih (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe the implementation of Bhinneka Tunggal Ika (Unity in Diversity) values in Civic Education (PKn) learning at SD Negeri 001 Sangatta Utara. These values serve as a fundamental basis for shaping students' character, especially in appreciating differences and maintaining unity. The study employs a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation. The findings indicate that Bhinneka Tunggal Ika values are integrated into learning through teaching materials, discussion activities, and collaborative projects. Additionally, teachers play an active role in instilling attitudes of tolerance, cooperation, and respect for diversity. However, several challenges remain, such as limited supporting learning media and a lack of parental involvement in reinforcing these values at home. This study recommends the development of diversity-based learning media and enhanced collaboration between schools and parents to effectively implement Bhinneka Tunggal Ika values.